Low Birth Weight and Inappropriate Feeding Variation Caused Nutritional Disorders Based on The Composite Index of Anthropometric Failure (CIAF) - Yanti, Eka Safitri; Yunus, Endriyani Martina (Universitas Airlangga, 2024)
Nutritional disorders in children contribute to both morbidity and mortality, with potential for hereditary diseases. Regular growth monitoring helps in early detection and prevention. The Composite Index of Anthropometric Failure (CIAF) is a tool used to assess multiple growth failures, making risk prediction more accurate. This study aims to identify determinants of nutritional disorders using CIAF. Conducted in Belitung Regency, Indonesia, from January to October 2024, the research involved 198 children aged 6 months to 5 years, selected via random sampling. Measurements of height and weight were analyzed according to WHO 2006 standards. Parental characteristics, birth weight, economic status, nutrition awareness, and clean living behaviors were assessed via questionnaires. Results showed that 40.4% of the children experienced growth failure, though none of the parental or child characteristics had a significant relationship with it. However, low birth weight (p=0.048) and variation in feeding menus (p=0.009) were significantly associated with stunting. Other factors, including parental height, family income, and nutrition awareness, showed no significant relationships with growth failure. In conclusion, low birth weight and diverse feeding practices play key roles in preventing stunting.